Personality in Soccer: Investigation of the Five-Factor Model of Personality in High-Level Athletes - Spielmann, Jan; Beavan, Adam; Mayer, Jan (Frontiers in Sports and Active Living, 2022)
Background: In high-level sports, rapid screening and diagnostic instruments are necessary considering limited access that researchers have to these athletes. In the area of sport psychological diagnostics, the NEO-FFI is a promising tool to gain information about an athlete’s personality traits. The current study investigated the NEO-FFI’s scientific quality criteria and general application to elite-level soccer. Methods: Personality traits of 378 elite-level soccer athletes were assessed using the NEO-FFI. Analysis focused on internal consistency, factor structure and gender differences. Additionally, a second measurement with a six-week interval was conducted with a sub-sample of 86 athletes to analyse test-retest reliability. Results: Overall, the results are in line with previous findings outside high-level sports. For the total sample, alpha-levels from .68 to .84 and intraclass correlation coefficients (ICC) for test-retest measures from .86 to .91 could be found. Item-level principal component analysis using both oblimin and oblique rotation showed better stability in neuroticism (N) and conscientiousness (C) than in extraversion (E), openness (O) and agreeableness (A). Gender differences could be found in values of internal consistency, ICC and NEO-FFI traits. Conclusion: The results of this study demonstrate good transferability of the NEO-FFI from settings outside high-level sports into this specific niche of sport psychological assessment. However, the same weaknesses of the applied instrument in general populations were also replicated in the sporting population.